Digital Leadership dan Organizational Agility dalam Meningkatkan Kinerja Lembaga Pendidikan - Melva Audina; Kinanti Dyah Ayu Puspita Retno Putri; Yaka Paweja; Kabri Kabri (Journal of Literature Review, 2026)
Digital transformation requires educational institutions to possess leadership capable of steering change and an organization agile enough to respond to environmental dynamics. This study aims to analyze the contributions of digital leadership and organizational agility to enhancing the performance of educational institutions and to develop a conceptual model integrating these two variables. A Systematic Literature Review (SLR) approach following the PRISMA 2020 protocol was employed, searching databases such as Scopus, Web of Science, ScienceDirect, SpringerLink, Emerald Insight, Taylor & Francis Online, Wiley Online Library, and IEEE Xplore—with Google Scholar as a supplementary source—for publications from 2020 to 2026. Out of 1,842 initial records, 84 articles met the inclusion and quality criteria for thematic synthesis. The analysis reveals that 91% of the studies report a significant positive relationship between digital leadership and organizational agility, 84% confirm the impact of digital leadership on educational institution performance, and 76% of studies examining mediation demonstrate that organizational agility acts as a connecting mechanism rather than merely a parallel predictor. Four key success factors for implementation were identified: information and communication technology infrastructure readiness, adaptive organizational culture, institutional policy support, and human resource digital literacy. The study's novelty lies in its integrated conceptual model, which positions organizational agility as a mediating variable, and the expansion of the research context to include religious educational institutions—such as Buddhist education—which have historically been underrepresented in the literature. This model can serve as a reference for digital transformation development strategies in Indonesian educational institutions.